Ladder of Life: Qualitative data collection tool to understand local perceptions of poverty dynamics - Petesch, Patti (International Maize and Wheat Improvement Center, 2018)
This resource examines GENNOVATE’s Ladder of Life exercise, a focus group tool conducted with poor women and men that explores their understandings and interpretations of the different wellbeing groups and poverty trends in their community, as well as the key factors and processes seen to shape these dynamics. The resource reviews the purpose of the tool, highlights key fieldwork procedures, and reproduces the interview guide.